학령기 경계선 지적 기능 아동의 읽기 하위영역별 특성 - 김주영(Ju Young Kim); 김자경(Ja Kyoung Kim) (언어치료연구, 2016)
목적: 본 연구는 학령기 경계선 지적 기능을 지닌 초등학교 학생들의 읽기 하위영역별 특성을 살펴보는 것을 목적으로 하였다. 방법: 본 연구의 대상은 총 89명으로 경계선 지적 기능 아동 45명, 평균 지능 아동 44명이다. 연구 대상은 학년에 따라 저학년(1-3학년) 경계선 지적 기능 집단, 고학년(4-6학년) 경계선 지적 기능 집단, 저학년(1-3학년) 평균 지능 집단, 고학년(4-6학년) 평균 지능 집단으로 분류하였다. 연구도구로 한국 웩슬러 아동용 지능 검사(K-WISC-Ⅳ)와 국립특수교육원 기초학력 검사(KNISE-BAAT)를 사용하였다. 자료분석을 위해 SPSS 18.0을 사용하여 빈도분석, 일원변량분석 및 사후검증을 실시하였다. 결과: 자료 분석 결과, 경계선 지적 기능 집단의 50.9%가 읽기 평균 수준에 미치지 못하였고, 15.6%가 학습지체 또는 심한 학습지체 수준으로 나타났다. 마지막으로 읽기 하위영역 중 음독능력, 낱말이해, 문장완성, 어휘선택, 문장배열, 짧은글이해 영역에서 네 집단에서 유의미한 차이가 나타났다. 결론: 경계선 지적 기능 아동은 해독과 단어 및 단순한 문장 수준에서 의미를 이해하는 독해능력은 초등 고학년이 되면 평균 지능 아동만큼 성취 가능하지만, 복잡한 구문 및 단락 수준에서 독해는 고학년이 되어도 또래 평균 지능 아동만큼 성취하는데 어려움을 보인다. 따라서 초등학교 고학년(4-6학년) 경계선 지적 기능 아동의 읽기 중재시 다양한 문장의 의미 및 구조, 문장 간 관계, 그리고 텍스트 구조를 이해하는데 초점을 둘 필요가 있다. 본 연구의 결과를 토대로 연구의 함의, 제한점 및 후속연구에 대한 제언을 하였다. Purpose: The purpose of this study was to examine the reading subdomain characteristics of elementary school students with borderline intellectual functioning (BIF). Methods: Eighty-nine subjects (45 children with BIF and 44 children with average intelligence) participated in this study. The subjects were classified into four groups: BIF 1st-3rd grade, BIF 4th-6th grade, average intelligence 1st-3rd grade, and average intelligence 4th-6th grade. The Korea Wechsler Intelligence Scale for Children (4th Ed) and the Korea National Institute for Special Education-Basic Academic Achievement Test (Reading) were administered to the participants. Frequency analysis, one-way ANOVA, and Scheffé Post Hoc test were conducted for data analysis using SPSS/Win 18.0. Results: As a result of the data analysis, 50.9% of the BIF group failed to meet the basic standard level in reading. Furthermore, under achievement and severe under achievement levels appeared 15.6% of the BIF group. Finally, there were significant differences between each group in reading aloud, word comprehension, sentence completion, vocabulary selection, sentence arrangement, and short text comprehension. Conclusions: According to the results of this study, BIF children can achieve reading abilities in aspects of decoding and reading comprehension in the level of word and simple sentence, but cannot achieve reading abilities in aspects of reading comprehension in the level of complex sentence or paragraph. Further study is required to comprehend the structures and meaning of various sentences and the relationship between sentences and text scheme in the reading intervention of 4th-6th grade students with BIF. Based on these findings, the implications and limitations of this study and suggestions for further studies were discussed. KCI Citation Count: 16